The Effect of Emotional Intelligence, Organizational Commitment and Organizational Citizenship Behavior on Employee Performance - Mohyi, Achmad (AIBPM Publisher, 2020)
The purpose of this study is to examine the effect of emotional intelligence, organizational commitment, and organizational citizenship behavior on employee performance. Sampling method was purposive sampling with 80 employees of PT. Taman Sengkaling UNMUH Malang. A multiple linear regression analysis was used to determine the effect of emotional intelligence, organizational commitment, and organizational citizenship behavior on employee performance. This study concluded that there is a significant effect between emotional intelligence, organizational commitment, and organizational citizenship behavior on employee performance. The higher the emotional intelligence, organizational commitment, and organizational citizenship behavior OCB, the higher the employee performance. This paper research suggests further research examine other variables with different research objects.